(untitled) (TAJ: Journal of Teachers Association, 2018)
Transitional cell carcinoma (TCC) comprises about 90% of all primary tumors of urinary bladder. The accuracy of multiple voided urine cytology justifies its continued use as a first line diagnostic and detection technique, particularly for high grade invasive cancers and clinically unsuspected case of carcinoma particularly carcinoma in-situ. In this study 57 cases were taken to see correlation of cytology, histology, stage, morphological pattern and sensitivity and specificity of urothelial cancers. Out of 57, 53 (92.99)% were positive for malignancy and 4(7.01%) were negative. There were 14 (24.56%) non-invasive papillary tumors, 1(1.76%) carcinoma in-situ and 42 (76.68%) invasive carcinoma of all grades and types. Of 14 grade-II non-invasive papillary tumors, 12 (85.72%) were cytologically positive. With only two exceptions, out of 39 all of the invasive carcinomas of all grades and types were identified by cytology as cancerous. A 100% positive cytology was noted in the detection of flat carcinoma in-situ, papillary adenocarcinoma and squamous cell carcinoma of the urinary bladder. Of the total 57 cases of malignant lesions of urinary tract, 53 (92.99%) were positive on cytological examination. The two TCC of the renal pelvis also gave a 100% positive cytologic results. Among invasive carcinoma, stage B1 and B2 urothelial cancers yield highest positive cytologic diagnosis rather than stage 0 and stage A urothelial cancers. For all tumors the sensitivity was 92.99%. The specificity was 100% since there were no false positive cases. The diagnostic accuracy was 93% (approximately). Comparison with previously published data this study showed highest diagnostic accuracy, sensitivity, specificity of voided urine cytology, good correlation with cytology histology and stage of tumor. So voided urine cytology, a very cheap and purely non invasive technique, can be done as an effective method to diagnose urothelial cancers in a developing country like Bangladesh where facilities for other investigations are practically limited. TAJ 2017; 30(1): 1-10